PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BAKRIE CONSTRUCTION BOJONEGARA - Syifa Firdiani; Furtasan Ali Yusuf; Basrowi Basrowi (Universitas Bina Bangsa, 2021)
Human resources in a company greatly affect the performance of the company, this can be seen from the performance produced by employees in the company. Providing appropriate compensation for their work can spur employees' enthusiasm to work better from time to time. Work discipline greatly affects employee performance, this is because discipline is a form of training for employees in implementing company rules, the more disciplined employees are, the more disciplined employees will be. also high employee work productivity and performance at the company. This study aims to determine the effect of compensation and work discipline on employee performance at PT. Bakrie Construction Bojonegara either partially or simultaneously. The research method used is a quantitative approach with the data used in the form of primary data and secondary data. With the total population used in this study were 34 employees of the engineering division. Determination of the sample using saturated sampling technique with a sample of 34 employees of the engineering division. Based on the results of hypothesis testing, it can be concluded that there is an influence between compensation and work discipline on employee performance at PT. Bakrie Construction Bojonegara partially or simultaneously.